Teachers' and Undergraduate Students' Perceptions of the Use of the Internet to Study English - Floris, Flora Debora (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2012)
The purpose of this study was to find out teachers' and undergraduate students' perceptions of the importance of using the Internet to study English. This was measured through the use of questionnaires distributed to 10 teachers and 100 students; and interviews conducted with 5 teachers and 20 students. Based on the findings, it was concluded that in learning English, students need interactions with their teachers and friends. To facilitate the interactions, the Internet, particularly the websites designed for learning English is a good alternative. However, it should not be the only instrument used to improve the learners' language proficiency. Numerous strategies teachers can choose to implement it are also recommended.